Microbial BMAA and the Pathway for Parkinson’s Disease Neurodegeneration - Nunes-Costa, Daniela; Magalhães, João Duarte; G-Fernandes, Maria; Cardoso, Sandra Morais; Empadinhas, Nuno (Frontiers in Aging Neuroscience, 2020)
The microbial neurotoxin β-N-methylamino-L-alanine (BMAA) is a natural non-proteinogenic diaminoacid produced by some microorganisms including several cyanobacteria. BMAA biomagnifies through the food chain in some ecosystems, accumulating for example in seafood such as shellfish, prawns and fish, common dietary sources of this toxin that may impart neuronal consequences. In addition to its excitotoxic potential, BMAA has been implicated in protein misfolding, aggregation and enzyme activity inhibition, and in neuroinflammation, all hallmark features of several neurodegenerative diseases. However, the precise molecular mechanisms of BMAA neurotoxicity remain to be elucidated in detail. Although BMAA is widely detected in its free form, more complex BMAA-containing molecules such as paenilamicin have been identified recently in an insect gut pathogen. However, the hypothetical production of BMAA by members of the human gut microbiota, for example by non-photosynthetic cyanobacteria (Melainabacteria), remains unknown. In any case, should BMAA reach the gut it may interact with cells of the mucosal immune system and neurons of the enteric nervous system and, as observed, target their mitochondria. Here we review the available evidence and hint on possible mechanisms by which chronic exposure to dietary sources of this microbial neurotoxin may drive protein misfolding and mitochondrial dysfunction with concomitant activation of innate immunity, chronic low-grade gut inflammation, and ultimately the neurodegenerative features observed across the gut-brain axis in Parkinson’s Disease.